1992
DOI: 10.1149/1.2069105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Heat‐Fin Materials and Design of a Common‐Pressure‐Vessel Nickel‐Hydrogen Battery

Abstract: The reversibility of the octanoate adsorption was assessed by stepping the potential from -1 to +1 V vs. SHE (positive sweep), and then back from +1 to -1 V (negative sweep), and measuring friction and inverse capacitance for a 0.1 w/o 'solution of octanoic acid (Fig. 8). Friction and capacitance displayed hysteresis between the sweeps, though both returned to a value near the original at the end of the negative sweep, indicating desorption of the octanoate film. ConclusionStatic friction, current, capacitance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The 3-D transient thermal analysis showed that the pin fins are in favor of decreasing the bulk temperature and improving the temperature uniformity. Kim and White [25] studied different materials such as copper, copper beryllium, silver, and sterling silver as heat-fin materials by using a 2-D thermal coupling model of NI-MH battery. The fin geometry (thickness and height) and spacing were tested and yielded an acceptable temperature gradient of the battery pack.…”
Section: Introductionmentioning
confidence: 99%
“…The 3-D transient thermal analysis showed that the pin fins are in favor of decreasing the bulk temperature and improving the temperature uniformity. Kim and White [25] studied different materials such as copper, copper beryllium, silver, and sterling silver as heat-fin materials by using a 2-D thermal coupling model of NI-MH battery. The fin geometry (thickness and height) and spacing were tested and yielded an acceptable temperature gradient of the battery pack.…”
Section: Introductionmentioning
confidence: 99%